Ischemic Stroke during Pregnancy and Puerperium. (26th December 2010) - Del Zotto, Elisabetta; Giossi, Alessia; Volonghi, Irene; Costa, Paolo; Padovani, Alessandro; Pezzini, Alessandro
Abstract : Ischemic stroke during pregnancy and puerperium represents a rare occurrence but it could be a serious and stressful event for mothers, infants, and also families. Whenever it does occur, many concerns arise about the safety of the mother and the fetus in relation to common diagnostic tests and therapies leading to a more conservative approach. The physiological adaptations in the cardiovascular system and in the coagulability that accompany the pregnant state, which are more significant around delivery and in the postpartum period, likely contribute to increasing the risk of an ischemic stroke. Most of the causes of an ischemic stroke in the young may also occur in pregnant patients. Despite this, there are specific conditions related to pregnancy which may be considered when assessing this particular group of patients such as pre-eclampsia-eclampsia, choriocarcinoma, peripartum cardiomiopathy, amniotic fluid embolization, and postpartum cerebral angiopathy. This article will consider several questions related to pregnancy-associated ischemic stroke, dwelling on epidemiological and specific etiological aspects, diagnostic issue concerning the use of neuroimaging, and the related potential risks to the embryo and fetus. Therapeutic issues surrounding the use of anticoagulant and antiplatelets agents will be discussed along with the few available reports regarding the use of thrombolytic therapy during pregnancy.